Exploring the Impacts of Digital Implantation on ICH’s Inheritance and Development with Empirical Study - Mo Bing; Xu Chao; Shafilla Subri; Ali Alshehan; Wang Li (Environment-Behaviour Proceedings Journal, 2025)
In the process of digitalization, intangible cultural heritage (ICH) projects face both opportunities and challenges. On the one hand, digital technology is transforming the inheritance and development of ICH projects; on the other hand, it also poses a risk of these projects disappearing. Regardless, digital technology is becoming a new means of showcasing ICH projects. This study collects quantitative data through questionnaires, employs descriptive analysis techniques, and is complemented by qualitative research methods. It aims to explore the impact of digital implementation on the inheritance and development of ICH projects through empirical research.